Competitive binding to the oligopeptide binding protein, OppA: in-trap cleanup in an Fourier transform ion cyclotron resonance mass spectrometer. - Freitas, M; Hendrickson, C; Marshall, A; Rostom, A; Robinson, C (2000)
This communication demonstrates that gentle infrared laser heating can remove unwanted buffer adducts from a gas-phase protein complex without dissociating the complex itself. Specifically, noncovalent complexes of the oligopeptide-binding protein, OppA, bound to either (Ala)3 or LysTrpLys were electrosprayed from aqueous buffer solution into a 9.4 tesla Fourier transform ion cyclotron resonance mass spectrometer. In addition to the intact complexes, several additional buffer adduct species were produced under the conditions of the experiment. Irradiation of the trapped ion population with a continuous-wave infrared CO2 laser at relatively low power (2.5 W) for 1 s dissociated the buffer adducts but retained the intact protein:peptide complexes. Adduct-free complex(es) were then readily identified, and signal-to-noise ratio also increased by an order of magnitude because the same number of protein ions are distributed over fewer species. Higher IR power (5 W for 1 s) dissociated the adduct-free complex(es) without internal fragmentation. The present in-trap clean-up technique may prove especially useful for identifying and screening the combinatorial library ligands most strongly bound to a receptor in the gas phase.